FAKTOR-FAKTOR YANG MEMPENGARUHI IBU DALAM PEMBERIAN ASI EKSKLUSIF DI DESA PUCANGANOM KECAMATAN GIRIWOYO KABUPATEN WONOGIRI - Aminingsih, Sri; Puti, Lucia Desi (KOSALA : Jurnal Ilmu Kesehatan, 2015)
Background Breastfeeding will ensure babies stay healthy and start life in the most healthy. Breastfeeding is actually not only allows the baby to grow up to be healthy physically, but also more intelligent, stable had a emotional, spiritual development, and positivesocial development. Riskesdas 2010 coverage of exclusive breastfeeding in Indonesia is still far from the world average and still very far from the target of Healthy Indonesia 2010. In rural districts Pucanganom Giriwoyo of the initial interview 3 of 5 mothers to breastfeed exclusively, while 2 others are not breastfed exclusively with reasons having to work, lack of time and because of no discharge of breast milk.The purpose to find out the factors that affect the mother in exclusive breast feeding in the village of Pucanganom sub-district of Giriwoyo Regency Wonogiri.Method of this research is descriptive research. While the plan is cross sectional used to find out the factors that affect the mother in exclusive breast feeding. Then there searchers took data from respondents regarding the factors that affect breast feeding.The Result Factors that affect the exclusive breast feeding is the age of the mother, the mother's education, number of children, mother's work and family income. The most exclusive breast feeding on mother's  age 26-45 years (83,33%), maternal education high school-undergraduate (70%), given on the first and second child(73,34%), employment of the mother as a homemaker (73,34%), and family income 1-3 million (76.67%).Conclusion the mother who does not work it's possible giving exclusive breast milk due to the considerable amount of time which can be used by the mother to nurture her baby even 24 hours time the mother could be given to her baby, therefore breast feeding can be done during the first 6 months of the birth of the baby.Keywords: Exclusive breast feeding